Implementation of Prenuptial Certificates as a Religious and State Effort in Forming a Sakinah Family - Wahdatul Ramdhani Husnan Taufiq; Imam Syafi’i; Hawa Hidayatul Hikmiyah (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
This journal discusses the implementation of premarital certificates as an effort made by religion and the state to form a sakinah family. This research uses a library research approach, meaning the research process or information search is carried out in the library or using literature sources and documents available in the library. This activity involves searching, identifying, and analyzing relevant sources of information. Apart from that, this research also uses a field research approach, meaning that data sources are taken from existing literature and from the field. The results of this research provide an in-depth understanding of the role of religion and the state in regulating marriage and offer valuable perspectives for legal practitioners, policy makers, and the general public interested in strengthening family values in society. As well as providing an understanding of the important role of pre-marital certificates in ensuring legality, protection and welfare for married couples and making it easier for the state to monitor and collect statistical data related to marriage and family.